The Shift of Character and Role of Minangkabau Women in Novel PEREMPUAN BATIH by A.R. RIZAL - Bulan Rara Yangsen; Inriati Lewa; Muhammad Syafri Badaruddin (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
This study aims to explain the shift in the nature and role of Minangkabau women in the novel Perempuan Batih by A. R. Rizal. This research uses the structural approach of the Teeuw model. The method used in this research is the qualitative method. Data collection is done through literature study by reading books and writings that have a relationship with the object of research. The types of data that will be used in this study are divided into two, namely primary data and secondary data. The results of the study describe that there is a shift in the nature and role of Minangkabau women in the novel Perempuan Batih which is seen through the depiction of Minangkabau women in the past and the depiction of Minangkabau women now in the novel Perempuan Batih by A. R. Rizal. Minangkabau women used to be described as women who hold fast to customs, are compassionate and loyal, tough and independent, good at cooking, and know the culture of Manggaleh. Minang women are now described as modern women, easily discouraged, and lose their identity. The depiction of Minangkabau women is examined through characterizations.